2019
DOI: 10.3390/su11040992
|View full text |Cite
|
Sign up to set email alerts
|

Research on Sharing Intention Formation Mechanism Based on the Burden of Ownership and Fashion Consciousness

Abstract: The sharing economy has become an important business model for China to promote energy conservation and emission reduction, improve the utilization efficiency of social resources, promote green and sustainable development, and achieve high-quality economic development. How to improve the willingness of individuals to share underutilized resources with others is becoming an urgent problem for enterprises and academia. Although current research on the sharing economy provides insights into users’ perspectives, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In the P2PA, empirical evidence postulates that economic benefit is one of the most extrinsic motivations (Tussyadiah, 2016) that plays a significant role in providers' compliant participation (Zhang et al, 2019). Gazzola et al (2019) conducted a study on Italian participants and found that monetary benefits positively impact participation in sharing economy.…”
Section: Extrinsic Motivation-economic Benefitmentioning
confidence: 99%
See 3 more Smart Citations
“…In the P2PA, empirical evidence postulates that economic benefit is one of the most extrinsic motivations (Tussyadiah, 2016) that plays a significant role in providers' compliant participation (Zhang et al, 2019). Gazzola et al (2019) conducted a study on Italian participants and found that monetary benefits positively impact participation in sharing economy.…”
Section: Extrinsic Motivation-economic Benefitmentioning
confidence: 99%
“…According to Sigala (2015), entrepreneurial freedom in the P2PA can be fostered when tourism suppliers have the desire to serve the tourists through marketplaces where the exchange of experiences and value can be made possible. Ahsan (2020) posits that P2PA enables providers to have the flexibility and freedom to choose when to work, how In the P2PA context, an opportunity is referred to as the circumstances that facilitate or restrain peer providers' involvement in the participation process of hosting tourists (Cui et al, 2020;Zhang et al, 2019). In a study by Syed Zwick (2020), multiple conditional factors have been identified that either facilitate or hinder individuals from participating in behavior, such as the availability of time, space, and resources like support from family/neighbors and the legal rules/regulations imposed by the government.…”
Section: Intrinsic Motivation-social Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jain and Mishra [45] stated that Indian millennials use luxury fashion rental services for conformity and status indulgence. Zhang et al [53] noticed that fashion consciousness influences the intention to use. Fifth, space saving means making sure that the consumer's closet space and personal space are not overtaken by bulky clothes.…”
Section: Perceived Benefit In Fashion Rental Servicesmentioning
confidence: 99%